2006
DOI: 10.1089/aid.2006.22.153
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CCR5, CCR2, CX3CR1, and SDF1 Polymorphisms in HIV-Positive Treated Patients: Impact on Response to HAART and on Peripheral T Lymphocyte Counts

Abstract: Although polymorphisms of chemokine genes (SDF1, stromal cell-derived factor-1 and RANTES, regulated on activation, normal T cell expressed and secreted) and chemokine-receptor genes (CCR5, CCR2, CX(3)CR1) were shown to be associated with sensitivity to HIV infection and untreated HIV disease progression, their association with the response to highly active antiretroviral therapy (HAART) remains unclear. To explore the possible influence of such polymorphisms on the evolution of AIDS in treated patients, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…78 Other genes. Genetic polymorphisms in the genes coding for the CXCR4-binding chemokine CXCL12 or SDF-1, 79 for the chemokine receptor CX3CR1, 79 and in genes located in the major histocompatibility complex 75,80 have also been linked to treatmentinduced CD4 ϩ T-cell restoration.…”
Section: Other Genetic Factorsmentioning
confidence: 99%
“…78 Other genes. Genetic polymorphisms in the genes coding for the CXCR4-binding chemokine CXCL12 or SDF-1, 79 for the chemokine receptor CX3CR1, 79 and in genes located in the major histocompatibility complex 75,80 have also been linked to treatmentinduced CD4 ϩ T-cell restoration.…”
Section: Other Genetic Factorsmentioning
confidence: 99%
“…[21][22][23][24] Multiple host genetic factors have also been found to influence CD4 T-cell recovery. [25][26][27][28][29][30][31] We recently demonstrated by using a multivariable model that IL-7Ra haplotype-2 was a significant predictor of more rapid CD4 T-cell recovery following suppressive cART in an Australian-based largely Caucasian HIVinfected cohort. 22 Consistent with observations in haplotype-2 carriers in HIV-uninfected cohorts, 9,11,32,33 we found that HIV-infected patients who were homozygous for haplotype-2 had significantly lower concentrations of sIL-7Ra compared with non-haplotype-2 carriers.…”
Section: Introductionmentioning
confidence: 99%
“…This protective effect of the GP was even more pronounced in individuals with longer durations of HIV infection. SDF1-3′-A was also recently reported to be more common in a cohort of HIV+ individuals who responded well to HAART compared to those whose viral loads remained elevated after one year (Puissant et al 2006). However, others have found contrasting results.…”
Section: Polymorphisms Of Chemokines and Chemokine Receptorsmentioning
confidence: 85%